Regulatory Shifts and Legal Certainty in Cryptocurrency Trading: Towards an Integrated Supervision Model in Indonesia - Berutu, Jundri R.; Yuhelson, Yuhelson; Prasetyo , Dedy Ardian (Pelopor Publikasi Akademika, 2025)
The rapid growth of cryptocurrency trading in Indonesia reflects the increasing integration of digital assets into the national economy. Initially classified as tradeable commodities under the supervision of the Commodity Futures Trading Regulatory Agency (BAPPEBTI), cryptocurrencies have recently been repositioned within the financial sector's regulatory framework, following the enactment of Law No. 4 of 2023 on Financial Sector Development and Strengthening (UU PPSK). This study analyzes the legal and institutional implications of shifting supervisory authority to Indonesia's Financial Services Authority (OJK) and examines the regulatory challenges in ensuring legal certainty within this evolving digital asset landscape. Using a normative legal research method with statutory, conceptual, and comparative approaches, the findings reveal that Indonesia’s regulatory landscape remains fragmented and transitional. The absence of a unified and substantive legal framework, combined with institutional overlap and limited technological oversight capacity, undermines investor protection and market integrity. This paper recommends the formulation of a dedicated cryptocurrency law, the adoption of digital supervision mechanisms, and strengthened inter-agency coordination to build a coherent and future-proof legal regime. The novelty of this research lies in its critical examination of Indonesia’s regulatory transition and its proposal for a unified digital asset governance model. The study contributes to the growing body of scholarship on digital financial regulation in emerging markets and offers practical guidance for policymakers navigating the complexities of crypto-asset supervision.